Green biocatalysis - Patel, Ramesh N., 1942- (Hoboken, NJ : John Wiley & Sons, 2016)
'This book describes the enzyme-driven syntheses of industrially important compounds and chiral intermediates for chemicals and pharmaceuticals. The chapters describe recent technological advances in enzymatic and microbial transformations and are written by internationally renowned scientists and professors. The synthesis of industrially important molecules is described from the starting substrate to the final product and includes detailed mechanisms. This book addresses the use of various types of reactions catalyzed by microbial cells or enzymes derived from microbes in the production of industrially useful compounds and a variety of drugs. The production of chiral alcohols, amines, unnatural amino acids, esters, carboxylic acids, epoxides, hydroxylated compounds and drug metabolites as well as recent advances in enzyme catalyzed acylation, dehalogenation, esterification, oxidation-reduction, transamination, deamination, C-N, C-C, C-O bond formation, Baeyer-Villegar reaction and aldol as well as acyloin condensation reactions are covered. Cutting-edge topics such as directed evolution by gene shuffling and enzyme engineering to improve biocatalysts will be presented. Enzyme immobilization and reusability studies and enzymatic protection and deprotection are addressed as well'--
Title Page; Copyright Page; Contents; Preface; About the Editor; Contributors ; Chapter 1 Biocatalysis and Green Chemistry ; 1.1 INTRODUCTION TO SUSTAINABLE DEVELOPMENT AND GREEN CHEMISTRY; 1.2 GREEN CHEMISTRY METRICS; 1.3 ENVIRONMENTAL IMPACT AND SUSTAINABILITY METRICS; 1.4 SOLVENTS; 1.5 THE ROLE OF CATALYSIS; 1.6 BIOCATALYSIS AND GREEN CHEMISTRY; 1.7 EXAMPLES OF GREEN BIOCATALYTIC PROCESSES; 1.7.1 A Chemoenzymatic Process for Pregabalin; 1.7.2 A Three-Enzyme Process for Atorvastatin Intermediate ; 1.7.3 Enzymatic Synthesis of Sitagliptin.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Enzymes -- Biotechnology; Biocatalysis; Green chemistry; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biocatalysis; Enzymes -- Biotechnology; Green chemistry; Electronic books